2020
DOI: 10.1177/0886260520958658
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of Sexual Consent among Heavy-drinking College Men

Abstract: The current study sought to examine how heavy-drinking college men describe communication of sexual interest and sexual consent. Thematic analysis of semi-structured interviews with 12 heavy-drinking college men identified three themes. Themes included: (a) expectations about parties and sexual activity, (b) observing and communicating sexual interest, and (c) communication of sexual consent. Men reported visiting drinking environments to locate women who they assumed would be open to sexual advances. In these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 68 publications
3
20
0
Order By: Relevance
“…This agrees with comparative qualitative studies that have concluded that alcohol is deliberately used by men as a seduction technique without considering whether or not there is consent (Orchowski et al, 2020). In fact, the phenomenon of men inciting women to drink so as to take sexual advantage of them should be considered as an aggressive rape tactic (Thompson and Cracco, 2008; Warkentin and Gidycz, 2007) and the perpetrator of such behaviour as “predatory” (Graham et al, 2010).…”
Section: Study Findingssupporting
confidence: 89%
See 2 more Smart Citations
“…This agrees with comparative qualitative studies that have concluded that alcohol is deliberately used by men as a seduction technique without considering whether or not there is consent (Orchowski et al, 2020). In fact, the phenomenon of men inciting women to drink so as to take sexual advantage of them should be considered as an aggressive rape tactic (Thompson and Cracco, 2008; Warkentin and Gidycz, 2007) and the perpetrator of such behaviour as “predatory” (Graham et al, 2010).…”
Section: Study Findingssupporting
confidence: 89%
“…It is noteworthy, moreover, that one of the young men interviewed should call these behaviours a common "tactic": "Well if I go out for ten nights then maybe there is one who has that tactic, to call it something, and so it's fairly usual…and not one person, but several (…) in that moment they (the girls) react nervously 'well no, no, no', but come on, if maybe he is by himself and she is by herself, then later you can regret it, but it's already done, you've also got to know how to drink (…) I think that as you're under the effect of alcohol, I don't know, I don't know if they consent or don't consent (…) A cousin of mine, fooling, fooling, fooling around, she kept quiet, and later the next morning she called me in tears, yes it's true, but it had already happened, what can you do, 'don't drink, I don't know'." (Lucas,18) This agrees with comparative qualitative studies that have concluded that alcohol is deliberately used by men as a seduction technique without considering whether or not there is consent (Orchowski et al, 2020). In fact, the phenomenon of men inciting women to drink so as to take sexual advantage of them should be considered as an aggressive rape tactic (Thompson and Cracco, 2008;Warkentin and Gidycz, 2007) and the perpetrator of such behaviour as "predatory" (Graham et al, 2010).…”
Section: Study Findings Violence and Alcohol In The Spanish Night-tim...supporting
confidence: 61%
See 1 more Smart Citation
“…That we did not corroborate previous findings regarding between-person sociodemographic variability of sexual consent may have been due to our sample comprising only people who were in committed sexual relationships. 2 Indeed, how people conceptualize sexual consent can vary based on relationship status (Humphreys & Brousseau, 2010;Orchowski et al, 2020;Righi et al, 2019), as can the ways they experience and communicate willingness to engage in sexual activity Marcantonio et al, 2018;Walsh et al, 2019). Because previous studies on the between-person variability of sexual consent collected data from samples that were much more heterogeneous than the present study regarding relational context, comparisons of between-person effects across studies must be done with caution.…”
Section: Discussionmentioning
confidence: 84%
“…Research indicates that nonverbal consent cues are used more frequently than verbal cues (Hickman & Muehlenhard, 1999 ; Orchowski et al., 2020 ; Righi et al., 2019 ). Despite the potential subtlety of nonverbal cues, qualitative evidence suggests that people are deft communicators when it comes to sex, effectively discerning their partners’ hints and behaviors as willingness or refusal (Beres, 2014 ; O’Byrne et al., 2008 ).…”
Section: Defining Sexual Consentmentioning
confidence: 99%